Current state of preconception care in sub-Saharan Africa: A systematic scoping review - Winifred C. Ukoha; Ntombifikile G. Mtshali; Lateef Adepeju (AOSIS, 2022)
Background: Preconception care (PCC) utilisation is essential to extend and complete the health continuum. However, these services are not yet incorporated into many low-income countries' existing maternal health services. Aim: This study aims to review the current literature on the knowledge, utilisation and provision of PCC. Setting: This included women and healthcare workers (HCWs) in Sub-Saharan African (SSA) countries. Methods: Arksey and O'Malley's scoping review methodology framework is used in this study. The following databases, Google Scholar, Science Direct, PubMed, Scopus and Dissertation via ProQuest, were searched. Articles that met the eligibility criteria were included in this study. Results: Out of the 451 retrieved articles, 39 were relevant. In most studies, women's utilisation and HCW's provision of PCC were considered limited. Their knowledge, however, varies between studies, and there were a few studies conducted among women with chronic conditions. Several factors influenced women and HCWs' knowledge, utilisation and provision of PCC, including age, level of education, employment, practice area, resources and knowledge. Preconception care interventions most commonly identified, utilised and provided were HIV testing, counselling and family planning, while preconception folic acid supplementation was the least. Conclusion: The estimates of knowledge and utilisation were suboptimal among women, while provision was the worst affected among HCWs. Gaps exist between the HCW knowledge and practice of PCC. There is a need to promote, prioritise, integrate and optimise the opportunistic provision of PCC in SSA. There is also a need for more studies on PCC provision and utilisation among women with chronic medical conditions.